Karakteristik Klinis Pasien Dengan Diagnosis Karsinoma Payudara Invasif Di Rumah Sakit Umum Daerah 45 Kuningan Tahun 2022-2024 - Iryanti, Erin; Larasati, Putri Ajeng Ayu; Pratamawati, Tiar M (Syntax Corporation, 2025)
Background: Invasive breast carcinoma refers to a large and heterogeneous group of malignant epithelial neoplasms originating from the glandular elements of the breast. Supportive examinations include anatomic pathology and immunohistochemistry for a more accurate diagnosis. Aim: To describe the clinical characteristics of patients with a clinical diagnosis of invasive breast carcinoma at the 45 Kuningan Hospital in 2022-2024. Method: This study used a descriptive observational approach from 2022 to 2024 at RSUD 45 Kuningan. A total sampling of 93 samples was used. Data were then analyzed to describe the frequency distribution of each variable.Results: Of the 93 samples of invasive breast carcinoma patients, the highest prevalence based on age was the most in the early elderly period, namely 46-55 with a percentage of (37.6%), female gender (100%), married status (100%), the most common occupation was housewife (93.5%), the most common location was unilateral (96.8%), the most common histopathological type was Invasive Carcinoma of No Special Type, with 73 patients (78.5%) and the most common molecular profile was Luminal B (16.1%).Conclusion: The highest prevalence of invasive breast carcinoma at RSUD 45 Kuningan is 46-55 years old, female, married with a housewife job, mostly unilateral location with the most histopathological picture of Invasive Carcinoma of No Special Type and the highest molecular profile of luminal B.